2008
DOI: 10.1103/physrevlett.100.217802
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Continuous Lehmann Rotation of Cholesteric Droplets Subjected to a Temperature Gradient

Abstract: In 1900, Otto Lehmann observed the continuous rotation of cholesteric drops when subjected to a temperature gradient. This thermomechanical phenomenon was predicted 68 years later by Leslie from symmetry arguments but was never reobserved to our knowledge. In this Letter, we present an experiment allowing quantitative analysis of the Lehmann effect at the cholesteric-isotropic transition temperature. More precisely, we measure the angular velocity of cholesteric drops as a function of their size and the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 13 publications
5
88
0
Order By: Relevance
“…By writing that this torque equilibrates with the viscous torque and by assuming that there is no flow of matter (we will come back later to this assumption), it was shown that the droplets rotate with an angular velocity ω given by [2,3] − νG γ 1 ω = 1 + drop e z · ∂ n ∂θ × n + ∂ n ∂θ 2 dV drop e z · ∂ n ∂θ × n + 1 − ( e z · n) 2 dV . (2) In this expression, e z is the unit vector parallel to the temperature gradient, θ the polar angle, and γ 1 the rotational viscosity. This equation shows that the texture angular velocity is proportional to G and has the form ω = −(1 + A)νG/γ 1 , where A is a dimensionless coefficient which depends on the director field and on the drop geometry.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…By writing that this torque equilibrates with the viscous torque and by assuming that there is no flow of matter (we will come back later to this assumption), it was shown that the droplets rotate with an angular velocity ω given by [2,3] − νG γ 1 ω = 1 + drop e z · ∂ n ∂θ × n + ∂ n ∂θ 2 dV drop e z · ∂ n ∂θ × n + 1 − ( e z · n) 2 dV . (2) In this expression, e z is the unit vector parallel to the temperature gradient, θ the polar angle, and γ 1 the rotational viscosity. This equation shows that the texture angular velocity is proportional to G and has the form ω = −(1 + A)νG/γ 1 , where A is a dimensionless coefficient which depends on the director field and on the drop geometry.…”
Section: Introductionmentioning
confidence: 98%
“…The experiment was first reproduced in 2008 by using a compensated cholesteric (mixture of octyloxycyanobiphenyl and cholesteryl chloride in equal proportions) [2,3] and 1 year later by using diluted cholesteric mixtures (i.e., nematic phase doped with a small amount of chiral molecules) [4,5]. In all of these experiments, the droplets coexist with their isotropic liquid and have a banded texture, indicating that the helical axis is rather perpendicular to the temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, molecular dynamics simulation of nematic phases of calamitic and discotic soft ellipsoids [17][18][19] clearly show that they orient perpendicularly and parallel, respectively, to the temperature gradient, so that the heat flow and thereby the energy dissipation rate are minimized. However, one system, where the director definitely orients perpendicularly to the temperature gradient, is the cholesteric liquid crystal, where the cholesteric axis orients parallel to the temperature gradient, so that the director becomes perpendicular to this gradient and the heat flow is minimized [1,2,[20][21][22]. This is also in agreement with the above-mentioned dissipation theorem even though the torque orienting the director is proportional to the square of the temperature gradient, whereas it is directly proportional to the velocity gradient in shear flow and elongational flow.…”
Section: Introductionmentioning
confidence: 99%